Prohibition of Application of Restorative Justice Regarding Cases of Corruption Crimes by Police Investigators - Denzel Andersson Cahyono (Daengku: Journal of Humanities and Social Sciences Innovation, 2023)
The purpose of this research is to examine why Indonesian Police Investigators forbid the use of restorative justice in situations involving criminal acts of corruption. This study was motivated by a desire to learn more about the history of restorative justice and its potential effects in the context of dealing with corruption cases. This research combines a normative legal perspective with a descriptive analytic technique. The information utilized is secondary, meaning it was gathered from other sources. The study's findings reveal that Indonesian Police Investigators cannot utilize restorative justice in situations involving criminal acts of corruption since it violates the law, particularly the principles of criminal law, and has the potential to violate human rights. To guarantee fair and effective law enforcement, there must be a greater knowledge of restorative justice and the establishment of a better legal system.